Kinerja Karyawan Divisi Sales Di PT. X Ditinjau Dari Motivasi Kerja - Andi Cahyadi; Matius Wahyu Bannon Tri Nugroho (Fakultas Psikologi Universitas Kristen Satya Wacana, 2024)
This research aims to find out the relationship between work motivation and employee performance in the sales division at PT. X Madiun. The method used in this research uses quantitative methods with relationship test analysis. The performance scale and work motivation scale are data collection tools used in this research. The respondents involved in this research were 40 employees, whose characteristics were employees who worked at PT. In this study, researchers used total sampling as a sampling technique, because there were less than 100 respondents. Pearson product moment was used in this study to analyze how strong the relationship between these two variables is. The research results obtained are a coefficient of r = 0.780 with p = 0.000 (p < 0.05) with a positive correlation direction, meaning that there is a significant relationship between work motivation and employee performance in the sales division at PT by PT X sales division employees, the higher their performance will be. Referring to the research results, a conclusion can be drawn that in order for the sales division employees at PT X to have good performance, what needs to be done is to increase their work motivation.